PERAN DAN BENTUK PENDAMPINGAN AYAH DALAM PERKEMBANGAN SOSIAL-EMOSIONAL ANAK: STUDI KUALITATAIF - Adelia Rahayu (Ash-Shobiy: Jurnal Pendidikan Islam Anak Usia Dini dan Al-Qur'an, 2026)
Early childhood social-emotional development is strongly influenced by the active role of fathers in parenting. The purpose of this descriptive qualitative study was to examine the forms, meanings, and contributions of fathers' mentoring from the perspective of children. Data were analyzed thematically through in-depth interviews with five fathers from diverse backgrounds. The results revealed six key techniques of father mentoring: providing quality time and emotional warmth, establishing open communication to manage emotions, implementing firm but caring parenting, instilling empathy through direct examples, providing support and appreciation to build self-confidence, and self-reflection as a model of emotional management. Significant interactions and active father presence create a supportive microenvironment and serve as a strong foundation for the social-emotional development of children aged four to six.